The Use of Song in Teaching English for Junior High School Student - Muhamad Sofian Hadi (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2019)
The aim of this study is to investigate in detail the use of song in teaching English for Junior High School student. This study is action researches conducted at Dharma Karya UT Junior High School class VII with participant number are 25 students. Data obtained from the result of test in each cycle. The findings showed that the learning process using song makes the students become more active in their interaction, it is showed by their participation level during the teaching is increased. Another finding also revealed that there is a significant improvement in the student’s English language skills using song from preliminary to cycle II stage in the research process. The average score of students at the preliminary stage is only 60 then it increased to 68 in the first cycle and increased significantly in cycle II with the amount of 80. It can be concluded that action research is done by using song in teaching English for Junior High School significantly helps the students in increasing their English language skills. This study recommends the continuation of using various teaching media and tools for Junior High School student in order to improve their English language skills.